Lateral flow immunoassay for the detection of perinatal and traumatic brain injury - Back, Elena (My University, 2026)
Perinatal and traumatic brain injuries are challenging to diagnose, yet both can lead to long‑term neurodegenerative disorders of varying severity. Rapid identification and accurate severity assessment are crucial, as timely treatment significantly improves outcomes. There is a need for sensitive blood-based laboratory test to enable reliable detection of brain injury, supporting faster clinical decisions and better patient care. The aim of this Master’s Thesis was to develop a quantitative lateral flow immunoassay (LFIA) for measurement of a brain injury related biomarker, Glial Fibrillary Acidic Protein (GFAP). Commercial mouse monoclonal anti-GFAP antibodies were used as capture and tracer antibodies in the assay. For signal measurement, the tracer antibody was conjugated to upconverting nanoparticles (UCNPs). The assay was optimized using commercial human GFAP spiked in 7.5 % BSA-TSA and human serum. A microtiter plate immunoassay for GFAP was developed to provide a reference method. The developed LFIA and microtiter plate immunoassay had the respective Limits of Detection of 110 pg/ml and 1.7 pg/ml GFAP in 7.5 % BSA-TSA, and 340 pg/ml and 3.3 pg/ml GFAP in human serum. Further optimization is required to alleviate the problems associated with nonspecific binding and low signal intensity, which had a negative effect on the LFIA sensitivity. The analytical sensitivity of the developed microtiter plate assay would, in theory, be sufficient for differentiating healthy individuals from those affected by brain injury. To confirm this, the performance of the microtiter plate assay should be further evaluated with patient samples.
Keywords: Perinatal brain injury; Traumatic brain injury; GFAP; Lateral flow immunoassay; UCNP